Seroprevalence of HIV, Hepatitis B, Hepatitis C and Syphilis at the Abidjan NBTC From January 2018 To December 2020 (Ivory Coast) (International Journal of Scientific Research and Management (IJSRM), 2022)
The objective of this study is to analyze the seroprevalence of HIV, hepatitis B, hepatitis C and syphilis at the National Blood Transfusion Center (NBTC) in Côte d’Ivoire from January 2018 to December 2020 in order to contribute to transfusion safety in Ivory Coast. Materials and Methods : This is a retrospective study that took place at the NBCT in Abidjan. This is a three year review covering the period from January 2018 to December 2020. Biological analyzes (AgHbs, anti-HCV Antibodies, HIV serology, syphilitic serology and blood group testing) were carried out on 469,863 blood donations. These were donors volunteers whose age was between 18 and 60 years old. The data was entered and analyzed on Excell 2012. The statistical tests used were Chi square. A value of p < 0.05 was considered statistically significant. Results : The prevalence of hepatitis B was the highest with 65.5‰, syphilis 1.6‰, HIV with 8.6‰ and Hepatitis C with 19‰. HIV prevalence was higher for new donations than for repeat donations. The difference was statistically significant. Conclusion : It would be important to make blood donors more aware of the modes of transmission of HIV, hepatitis C and syphilis. Blood donors should also be encouraged to vaccinate against hepatitis B.